EVALUASI POLA PEMUKIMAN DAN IDENTIFIKASI ZONA RAWAN BENCANA LETUSAN GUNUNG API GAMALAMA DI KECAMATAN TERNATE UTARA - Farika, Azmy; Rahim, Mustamin; Gaus, Abdul; Sultan, Mufti Amir (STABILITA || Jurnal Ilmiah Teknik Sipil, 2024)
Study of the distribution pattern of residential areas in North Ternate District to identify disaster-prone zones. The study of the distribution of residential areas is an effort to create conditions for better structuring of residential distribution in the future. Therefore, land use must be as optimal as possible in order to create good space for movement and optimize community welfare activities. North Ternate District is in an area prone to type I and type II volcanic disasters, namely a radius of 4.5 km from the crater of Mount Gamalama. This has an impact on the availability of land to be developed as a residential development plan. Based on the description of the problem above, the objectives of this research are: Analyzing the distribution pattern of residential areas in North Ternate District, and analyzing disaster-prone zones and the number of residential buildings at risk of disaster due to the condition of the residential distribution pattern. This research uses nearest neighbor analysis and spatial analysis. Based on the research results, it was found that there were random distribution patterns and clustered distribution patterns and the number of buildings spread across the disaster-prone zone II in North Ternate District was 282 residential buildings for residents